Long-term winter-site fidelity in Song Sparrows (Melospiza melodia). (23rd April 2019) - Kelly, Tosha R; Hobson, Keith A; Casbourn, Garth W; MacDougall-Shackleton, Elizabeth A; MacDougall-Shackleton, Scott A
Abstract: In migratory animals, the degree to which individuals return to the same wintering sites across multiple years can affect fitness and population dynamics, and thus has important implications for conservation. Despite this, long-term evaluations of wintering-site fidelity are rare for migratory birds: many populations are intensively studied on their breeding grounds but tracking the migratory movements of small birds once they leave the breeding grounds is challenging. To evaluate patterns of overwintering location and fidelity, we collected winter-grown claw tissue from 301 Song Sparrows ( Melospiza melodia ; 449 samples) captured in spring at their breeding grounds over 6 consecutive yr and assessed stable hydrogen isotope (δ 2 Hc ) values to determine within-individual repeatability and between-year variation in wintering latitudes. We also retrieved useable data from 8 geolocators over 2 consecutive winters. Geolocator-derived wintering positions correlated with origins based on δ 2 Hc values. Consistent with previous findings, male δ 2 Hc values reflected more northerly wintering areas than those of females, indicating shorter latitudinal migration distances for males, but the magnitude of the sex difference varied across years. The distribution of wintering latitudes was generally consistent among years, except for the 2015 舑2016 winter, which had unusually negative δ 2 Hc values. Values of δ 2 Hc were repeatable for males but not for females, suggesting that winter-site fidelity could differ between sexes. The data presented here emphasize the importance of tracking migratory populations across multiple years to uncover factors affecting population dynamics.